Setting definitions of childhood asthma in epidemiologic studies - Silva, D (2019)
Background: The definitions of childhood asthma differ among epidemiological studies. We aimed to compare the diagnostic accuracy and agreement of previous asthma definitions and to evaluate questionnaire-driven asthma definition patterns. Methods: Data on 808 participants aged 7-12 years from 20 schools were analyzed. Asthma definitions based on symptoms assessed by questionnaire, parent-reported medical asthma diagnosis, current use of asthma medication, airway reversibility after bronchodilatation, and increased (35 ppb) levels of exhaled nitric oxide (eNO) were compared with a gold standard (medical diagnosis of asthma with asthma symptoms in the past 12 months and/or airway reversibility). Concordance was assessed by Cohen's kappa. Data-driven analysis was applied to the questionnaire, and six scores were determined asthma, rhinitis, cough, non-specific respiratory symptoms, treated asthma, and uncontrolled asthma. Tree decisions were built using these scores. Results: Definitions of asthma based on respiratory symptoms, airway reversibility, and parent-reported medical diagnosis had a low sensitivity but high specificity. Agreement between reported and objective measures was poor. Parent-reported medical asthma diagnosis, but not reversibility or eNO, was able to predict questionnaire-driven symptom patterns. Decision trees indicated that those with recent non-specific respiratory symptoms had a higher probability of positive bronchodilation. Conclusion: A standardized operational definition of asthma should include a composite score based on reported asthma medical diagnosis, symptoms, and lung function. (c) 2019 EAACI and John Wiley and Sons A/S. Published by John Wiley and Sons Ltd.